Comparison and evolutionary analysis of Brassica nucleotide binding site leucine rich repeat (NLR) genes and importance for disease resistance breeding. Issue 1 (11th November 2020) - Zhang, Yueqi; Edwards, David; Batley, Jacqueline
Abstract: The Brassica genus contains many agriculturally significant oilseed and vegetable crops, however the crop yield is threatened by a range of fungal and bacterial pathogens. Nucleotide Binding Site Leucine Rich Repeat (NLR) genes play important roles in plant innate immunity. The evolution of NLR genes is influenced by genomic processes and pathogen selection. At the whole genome level, whole genome duplications (WGDs) generate abundant gene copies, most of which are lost during genome fractionation. At sub‐genomic levels, some retained copies undergo duplication forming clusters which facilitate rapid evolution through recombination. The number, distribution and genetic variations of the NLR genes vary among Brassica species and within populations suggesting differential selection pressure exerted by pathogen populations throughout the evolutionary history. A study of the evolution of disease resistance genes in agriculturally important plants such as Brassicas helps gain insights into their function and inform the identification of resistance genes for breeding of resistant lines. Core Ideas: The evolution of NLR genes in Brassicas is shaped by whole genome duplication, subgenomic duplication and recombination, and pathogen selection Abundant gene copies generated during whole genome duplications are lost Subgenomic duplication leads to uneven clustered distribution of the genes Subgenomic duplication and recombination create genetic variations The number, distribution and genetic variation of the NLR genes are under the influence of pathogen populations